Development of the LAPOR PAK System for Pre-Anesthesia and Patient Condition Information to Enhance Anesthesia Service Quality - Kurniawati, Ayu Khuzaimah; Yanto, Arief; Ernawati, Ernawati (University of Muhammadiyah Semarang, 2024)
Information technology systems play a crucial role in enhancing efficiency within nursing services, particularly in minimizing administrative tasks related to patient care. Anesthesia services hold a paramount position in hospital operations, focusing significantly on patient safety through the management of preoperative conditions. This study aims to develop a computer-based information technology system, named LAPOR PAK, for reporting preoperative patient conditions. The system is designed to improve anesthesia practices, thereby reducing adverse events and promoting patient safety. The research utilized the Research and Development (R&D) methodology, implementing the Systems Development Life Cycle (SDLC) to construct the LAPOR PAK system. The development process involved iterative testing and refinement to ensure functionality and usability. The outcome of the study is the LAPOR PAK system, which successfully facilitates the reporting of pre-anesthesia patient conditions. Testing revealed no data processing errors, with 20% of respondents rating the interface as good and 80% as very good. These findings underscore the system's effectiveness and utility in enhancing anesthesia services. The computer-based LAPOR PAK system represents a significant advancement in leveraging information technology to achieve patient safety goals in anesthesia. By streamlining preoperative reporting, the system not only minimizes adverse events but also supports routine monitoring and evaluation activities within healthcare settings.